Estimation of vortex-ultrasonic assisted extract of Anghoozeh Ferula Asafetida in green synthesized silver nanoparticles - Mina Nouraddini; Mashaallah Rahmani (Results in Chemistry)
This study aims to assay a novel model for assessing the phytosynthesis of silver nanoparticles using experimental design, vortexing, and Anghoozeh Ferula Asafetida plant extract (AFAPE@AgNPs). To ensure maximum sensitivity and accuracy, multivariate approaches were employed for modeling and optimizing the process conditions, aiming for a cost-effective procedure. The aqueous extract of the Ferula Asafetida plant served both as a capping agent and a factor for silver ion regeneration, facilitating the green production of silver nanoparticles. The optimization involved considering the simultaneous effects and mutual influences of various factors on the biosynthesis process. The optimal conditions identified were: an ultrasonic time of 43 min, pH of 7.8, Ferula Asafetida plant extract concentration equivalent to 4.4 % v/v, silver nitrate solution concentration of 3.7 mM, and a temperature of 56 degrees Celsius. Under the best conditions, the validation error varied between 1.62 % and 2.24 %, within the acceptable range for the quadratic model in the biosynthesis of AFAPE@AgNPs. The results showed that AgNP had the best absorption at 420 nm, an average size of 20–25 nm, and a spherical and uniform shape. After the characterization of AgNPs, their antimicrobial activity assessment against four bacterial strains: Bacillus cereus, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa was investigated.